Institutional Change, Political Economy, and State Capabilities : Learning from Edo State, Nigeria - Bain, Katherine; Porter, Doug; Watts, Michael (World Bank, Washington, DC, 2015)
This paper is one of a series aimed at deepening the World Bank’s capacity to follow through on commitments made in response to the World Development Report (WDR) 2011, which gave renewed prominence to the nexus between conflict, security, and development. Nigeria is a remarkable illustration of how deeply intractable the cycle of poverty, conflict, and fragility can become when tied to the ferocious battles associated with the political economy of oil. This paper places the corpus of analytic and programmatic work concerning institutional reform in conversation with a now substantial body of work on resource politics and most especially, the debate over the politico-institutional character (sometimes called political settlements or pacting arrangements associated with the order of power) and reform landscape of the petro-state. Recent institution reform policy writing appears to have little to say about the political and economic conditions in which crises and institutional disjunctures may authorize, and thereby enable, agents to embark on institutional reforms. The authors focus on Edo state for two reasons. First, it does not on its face appear to be an obvious location in which to explore a reform experience, given its entanglement in the Niger Delta conflict and the maladies typically associated with state fragility. Second, Edo is of interest also because of the changes that its experience is contributing to the World Bank country team’s effort to engage operationally across all its instruments with the political economy of institutional reform in Nigeria, its largest client country in Africa.